2019
DOI: 10.3390/ma12111759
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D Cellular Composites with Stem Cells Derived from Adipose Tissue and Endothelial Cells by Use of Optical Tweezers in a Natural Polymer Solution

Abstract: To better understand the regulation and function of cellular interactions, three-dimensional (3D) assemblies of single cells and subsequent functional analysis are gaining popularity in many research fields. While we have developed strategies to build stable cellular structures using optical tweezers in a minimally invasive state, methods for manipulating a wide range of cell types have yet to be established. To mimic organ-like structures, the construction of 3D cellular assemblies with variety of cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…As shown in the above molecular systems, cells can be cooperatively well-organized into ordered assemblies through the use of macromolecular crowding. Yoshikawa and co-workers showed that, in dextran solution, mammalian cells can be firmly deposited with the desired arrangement using optical manipulation (Hashimoto et al 2016;Yoshida et al 2017;Yamazaki et al 2019). Moderate crowding generated by dextran in the exterior provides an opportunity for rearrangement through which cell-cell association in the assembly can be reinforced.…”
Section: Toward Higher Hierarchical Cell Assemblymentioning
confidence: 99%
“…As shown in the above molecular systems, cells can be cooperatively well-organized into ordered assemblies through the use of macromolecular crowding. Yoshikawa and co-workers showed that, in dextran solution, mammalian cells can be firmly deposited with the desired arrangement using optical manipulation (Hashimoto et al 2016;Yoshida et al 2017;Yamazaki et al 2019). Moderate crowding generated by dextran in the exterior provides an opportunity for rearrangement through which cell-cell association in the assembly can be reinforced.…”
Section: Toward Higher Hierarchical Cell Assemblymentioning
confidence: 99%
“…The processing time of 10 s is sufficient for cell assembly; this is a shorter duration than that of the previous studies on cell assembly. [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The design flexibility of the microtool potentially allows us to align individual cells into a cell cluster with desired positions and with a specific number of cells. There are several studies that have observed cell‐cell interactions and co‐culture micro‐environments by assembling cells, including those based on polymer solution, [ 28 ] and cell surface treatment. [ 31 ] The technique proposed here has advantages in terms of its assembly speed (i.e., ∼5 s) and selective cell capture and handling by antibody function.…”
Section: Resultsmentioning
confidence: 99%